pH dependent self-assembly of dimetallic lanthanide complexes. - Faulkner, S; Burton-Pye, B (2005)
pH dependent self-association has been observed in a series of DO3A-derived lanthanide complexes bearing a carboxylate group that can act as a bridging ligand at high pH, switching on the luminescence from the lanthanide.